(untitled) (Global Journal of Human-Social Science, 2020)
This paper builds on previous research on gender in global politics, it engages with the epistemological issue of male dominance in the discourse of international relations and how that shapes international politics. The essay argues that explanations of inter-state relations that focus exclusively on the role of men are insufficient to explain global politics, as they fail to account for the impacts of wars and conflicts on women and misses the role of feminism in peace-building. The essay not only demonstrates that the propensity for wars and conflicts works differently for men than for women but also challenges the conventional wisdom that global politics is gender blind. The essay permits us to sharpen our understanding of the inefficiencies and insufficiencies of popular political theories while pointing to new interpretations of, and future avenues for, empirical research on global politics.